Oct 18 08:00 AM PDT  09:00 AM PDT Learn an intuitive, systematic approach that will maximize your success on Fillintheblank GMAT CR Questions. Oct 19 07:00 AM PDT  09:00 AM PDT Does GMAT RC seem like an uphill battle? eGMAT is conducting a free webinar to help you learn reading strategies that can enable you to solve 700+ level RC questions with at least 90% accuracy in less than 10 days. Sat., Oct 19th at 7 am PDT Oct 20 07:00 AM PDT  09:00 AM PDT Get personalized insights on how to achieve your Target Quant Score. Oct 22 08:00 PM PDT  09:00 PM PDT On Demand for $79. For a score of 4951 (from current actual score of 40+) AllInOne Standard & 700+ Level Questions (150 questions) Oct 23 08:00 AM PDT  09:00 AM PDT Join an exclusive interview with the people behind the test. If you're taking the GMAT, this is a webinar you cannot afford to miss!
Author 
Message 
TAGS:

Hide Tags

Senior Manager
Joined: 21 Dec 2009
Posts: 457
Concentration: Entrepreneurship, Finance

Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
Updated on: 30 Nov 2012, 02:41
Question Stats:
39% (02:42) correct 61% (02:14) wrong based on 721 sessions
HideShow timer Statistics
Let the function g(a, b) = f(a) + f(b). For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)? A: x +3 B: x^2 C: x D: 1/x E: x/4
Official Answer and Stats are available only to registered users. Register/ Login.
_________________
KUDOS me if you feel my contribution has helped you.
Originally posted by gmatbull on 29 Nov 2012, 19:17.
Last edited by Bunuel on 30 Nov 2012, 02:41, edited 1 time in total.
OA added.




Math Expert
Joined: 02 Sep 2009
Posts: 58435

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
30 Nov 2012, 03:02
Let the function g(a, b) = f(a) + f(b).
For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?A: x +3 B: x^2 C: x D: 1/x E: x/4 We can use plugin method to solve this question. Since \(g(a, b) = f(a) + f(b)\), then: \(g(a + b, a + b)=f(a+b)+f(a+b)=2f(a+b)\); \(g(a, a) + g(b, b)=f(a)+f(a)+f(b)+f(b)=2f(a)+2f(b)\). Thus the question asks: for which function f below will \(2f(a+b)=2f(a)+2f(b)\) > \(f(a+b)=f(a)+f(b)\)? Say a=1 and b=1, then the question becomes: for which function f below will \(f(0)=f(1)+f(1)\). A: x +3\(f(0)=0+3=3\) \(f(1)+f(1)=(1+3)+(1+3)=6\) No match. B: x^2\(f(0)=0^2=0\) \(f(1)+f(1)=(1)^2+(1)^2=2\) No match. C: x\(f(0)=0=0\) \(f(1)+f(1)=1+1=2\) No match. D: 1/x\(f(0)=\frac{1}{0}=undefined\) \(f(1)+f(1)=\frac{1}{1}+\frac{1}{1}=0\) No match. E: x/4\(f(0)=\frac{0}{4}=0\) \(f(1)+f(1)=\frac{1}{4}+\frac{1}{4}=0\) Match. Answer: E. Hope it's clear. forwhichofthefollowingfunctionsisfabfbfa124491.htmlforwhichofthefollowingfunctionsfisfxf1xfor85751.htmlfunctionsproblemneedhelp93184.htmlHope it helps.
_________________




VP
Joined: 02 Jul 2012
Posts: 1105
Location: India
Concentration: Strategy
GPA: 3.8
WE: Engineering (Energy and Utilities)

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
29 Nov 2012, 22:55
gmatbull wrote: Let the function g(a, b) = f(a) + f(b).
For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?
A: x +3 B: x^2 C: x D: 1/x E: x/4
OA to be posted later. The question is basically asking for which function f(a + b) = f(a) + f(b) A)\(LHS = a + b + 3\) \(RHS = a + 3 + b + 3 = a + b + 6.\) Not equal B)\(LHS = (a + b)^2\) \(RHS = a^2 + b^2\) Not equal C)\(LHS = a + b\) \(RHS = a + b\) If a & b are of different polarity not equal. D)\(LHS = \frac{1}{a + b}\) \(RHS = \frac{1}{a} + \frac{1}{b}\) Not equal E)\(LHS = \frac{a + b}{4}\) \(RHS = \frac{a}{4} + \frac{b}{4} = \frac{a + b}{4}\). Equal. Answer should be E
_________________




Senior Manager
Joined: 21 Dec 2009
Posts: 457
Concentration: Entrepreneurship, Finance

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
30 Nov 2012, 03:52
Bunuel and MacFauz, your explanations make a lot of sense. More so, Bunuel, you took time to explain the breakdown. Thanks.
_________________
KUDOS me if you feel my contribution has helped you.



Intern
Joined: 29 May 2013
Posts: 21
Concentration: Marketing, Entrepreneurship
GMAT Date: 08202014
GPA: 3.34

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
02 May 2014, 00:08
Bunuel wrote: From 100 hardest questions.
Bumping for review and further discussion. let a = 1 and b = 2, a+b = 3 A) x+3, 2(a+b+3) = 2(a+3) + 2(b+3) 2(a+b+3) = 2(a+b+3) + 6 [Can never be true] B) x^2 2(a+b)^2 = 2(a^2)+2(b^2) [Can/Cannot be true] C)x 2a+b = 2a + 2b [Can/Cannot be true] D)1/x 2/(a+b) = (2/a)+(2/b) = 2(a+b)/ab [Can/Cannot be true] E)x/4 2*(a+b)/4 = 2(a/4) + 2(b/4) = 2(a+b)/4 [Always true] Ans 'E'



Intern
Joined: 13 Dec 2013
Posts: 35

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
04 Jun 2014, 04:18
g(a+b,a+b) = g(a,a)+g(b,b) = f(a) + f(a) + f(b) + f(b)= 2f(a) + 2f(b) = RHS g(a+b,a+b) = f(a+b)+f(a+b) = 2f(a+b) = LHS
We divide by 2 both RHS and LHS and get
f(a+b)=f(a) + f(b)
I have an issue here: how do I know what to plug in from the answer choices? Since those are expressed in terms of X.
My approach was to take both a and b as the answer choice, but I don´t know if that is correct.
For d)
LHS: f(x/4 + x/4) = x/2 RHS: f(x/4) + f(x/4) = x/2
I'm sure i'm conceptually missing something.
Thanks.



Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 9706
Location: Pune, India

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
04 Jun 2014, 21:19
Enael wrote: g(a+b,a+b) = g(a,a)+g(b,b) = f(a) + f(a) + f(b) + f(b)= 2f(a) + 2f(b) = RHS g(a+b,a+b) = f(a+b)+f(a+b) = 2f(a+b) = LHS
We divide by 2 both RHS and LHS and get
f(a+b)=f(a) + f(b)
I have an issue here: how do I know what to plug in from the answer choices? Since those are expressed in terms of X.
My approach was to take both a and b as the answer choice, but I don´t know if that is correct.
I am not sure what you mean by this last line but I can help you with the various variables. The options (x+3), x^2 etc are the values of the function f(x) Option (A) tells you that f(x) = x + 3 So if you want to find f(a) or f(b) or f(a+b), it is quite simple. If f(x) = x+3, f(a) = a+3 If f(x) = x+3, f(a+b) = a+b+3 etc Wherever you have x in the expression you put a or a+b or b as the case may be. In this question, since options give the function f(x), you convert the entire g(x) into f(x). You get that you need to find the function f(x) such that f(a+b) = f(a) + f(b) The sum of individual functions of a and b and should be equal to the function of (a+b). We should look for an option where x is in the numerator and there is no addition/subtraction. So the first option I will try is (E) If f(x) = x/4, f(a) = a/4, f(b) = b/4, f(a+b) = (a+b)/4 f(a) + f(b) = a/4 + b/4 = (a+b)/4 Hence, for option (E), f(a+b) = f(a) + f(b) Answer (E)
_________________
Karishma Veritas Prep GMAT Instructor
Learn more about how Veritas Prep can help you achieve a great GMAT score by checking out their GMAT Prep Options >



SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1749
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
04 Jun 2014, 23:11
g(a + b, a + b) = g(a, a) + g(b, b) LHSg(a + b, a + b) = f(a+b) + f(a+b) = 2f(a+b) RHSg(a, a) + g(b, b) = f(a) + f(a) + f(b) + f(b) = 2f(a) + 2f(b) LHS = RHS 2f(a+b) = 2f(a) + 2f(b) f(a+b) = f(a) + f(b) \(\frac{a}{4} +\frac{b}{4} = \frac{a+b}{4}\) Answer =E
_________________
Kindly press "+1 Kudos" to appreciate



Intern
Joined: 14 May 2014
Posts: 39
GPA: 3.11

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
23 Jul 2015, 03:21
Bunuel wrote: Let the function g(a, b) = f(a) + f(b).
For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?A: x +3 B: x^2 C: x D: 1/x E: x/4 We can use plugin method to solve this question. Since \(g(a, b) = f(a) + f(b)\), then: \(g(a + b, a + b)=f(a+b)+f(a+b)=2f(a+b)\); \(g(a, a) + g(b, b)=f(a)+f(a)+f(b)+f(b)=2f(a)+2f(b)\). Thus the question asks: for which function f below will \(2f(a+b)=2f(a)+2f(b)\) > \(f(a+b)=f(a)+f(b)\)? Say a=1 and b=1, then the question becomes: for which function f below will \(f(0)=f(1)+f(1)\). A: x +3\(f(0)=0+3=3\) \(f(1)+f(1)=(1+3)+(1+3)=6\) No match. B: x^2\(f(0)=0^2=0\) \(f(1)+f(1)=(1)^2+(1)^2=2\) No match. C: x\(f(0)=0=0\) \(f(1)+f(1)=1+1=2\) No match. D: 1/x\(f(0)=\frac{1}{0}=undefined\) \(f(1)+f(1)=\frac{1}{1}+\frac{1}{1}=0\) No match. E: x/4\(f(0)=\frac{0}{4}=0\) \(f(1)+f(1)=\frac{1}{4}+\frac{1}{4}=0\) Match. Answer: E. Hope it's clear. forwhichofthefollowingfunctionsisfabfbfa124491.htmlforwhichofthefollowingfunctionsfisfxf1xfor85751.htmlfunctionsproblemneedhelp93184.htmlHope it helps. here i got confused because the given function "g" had 2 input variables whereas all option choices had single variable. it did not strike me that function g can be completely written in form of f. any tips on this..? how to avoid this or what shd be the line of thinking..?



Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 9706
Location: Pune, India

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
23 Jul 2015, 04:26
riyazgilani wrote: here i got confused because the given function "g" had 2 input variables whereas all option choices had single variable. it did not strike me that function g can be completely written in form of f. any tips on this..? how to avoid this or what shd be the line of thinking..?
Yes, the tip is very simple: read the question very carefully. Note that it says: For which function f below ... So basically what you are given below (in options) is function f. So obviously it will have a single input. Now you want certain condition in g to hold. Since you know the equivalency of f and g, convert g to f and you know which condition f should hold. Hope it makes sense.
_________________
Karishma Veritas Prep GMAT Instructor
Learn more about how Veritas Prep can help you achieve a great GMAT score by checking out their GMAT Prep Options >



Intern
Joined: 04 Sep 2014
Posts: 3
Location: India
Concentration: Operations, Other

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
03 Nov 2016, 23:54
Bunuel wrote: Let the function g(a, b) = f(a) + f(b).
For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?A: x +3 B: x^2 C: x D: 1/x E: x/4 We can use plugin method to solve this question. Since \(g(a, b) = f(a) + f(b)\), then: \(g(a + b, a + b)=f(a+b)+f(a+b)=2f(a+b)\); \(g(a, a) + g(b, b)=f(a)+f(a)+f(b)+f(b)=2f(a)+2f(b)\). Thus the question asks: for which function f below will \(2f(a+b)=2f(a)+2f(b)\) > \(f(a+b)=f(a)+f(b)\)? Say a=1 and b=1, then the question becomes: for which function f below will \(f(0)=f(1)+f(1)\). A: x +3\(f(0)=0+3=3\) \(f(1)+f(1)=(1+3)+(1+3)=6\) No match. B: x^2\(f(0)=0^2=0\) \(f(1)+f(1)=(1)^2+(1)^2=2\) No match. C: x\(f(0)=0=0\) \(f(1)+f(1)=1+1=2\) No match. D: 1/x\(f(0)=\frac{1}{0}=undefined\) \(f(1)+f(1)=\frac{1}{1}+\frac{1}{1}=0\) No match. E: x/4\(f(0)=\frac{0}{4}=0\) \(f(1)+f(1)=\frac{1}{4}+\frac{1}{4}=0\) Match. Answer: E. Hope it's clear. forwhichofthefollowingfunctionsisfabfbfa124491.htmlforwhichofthefollowingfunctionsfisfxf1xfor85751.htmlfunctionsproblemneedhelp93184.htmlHope it helps. I was trying to solve the same problem with values a=2 and b=3, therefore then the question becomes: for which function f below will \(f(5)=f(2)+f(3)\). Based on this I observed that for option C:x, f(5)=5=5 and f(2)+f(3)=2+3=2+3=5 now I know the OA is E and the functions are equal for option E, but am I missing something in option C, it would be great if someone could shed some light on this.



Intern
Joined: 17 Sep 2017
Posts: 2
Location: United States (HI)
GPA: 3.06

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
11 Oct 2017, 01:09
Even I fully understand how to solve this problem, I don't think I can get the answer in 2 mins.... TOO MUCH CALCULATION



Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 9706
Location: Pune, India

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
11 Oct 2017, 03:43
patrickpeng wrote: Even I fully understand how to solve this problem, I don't think I can get the answer in 2 mins.... TOO MUCH CALCULATION A little bit of forethought will help you solve it quickly. You want: g(a + b, a + b) = g(a, a) + g(b, b) In the expression, you want that when you put a+b, it should be the same as when you put a and b individually. A: x +3 B: x^2 C: x D: 1/x E: x/4 Of the given options, x^2 may not be it since (a+b)^2 is not same as a^2 + b^2. Similarly, a+b is not the same as a + b In such questions, with x in the denominator, you certainly cannot split 1/(a+b) as 1/a + 1/b. I will try option (E) first since it has a multiplication (x * 1/4). We know that (a+b)*1/4 = a*(1/4) + b*(1/4)
_________________
Karishma Veritas Prep GMAT Instructor
Learn more about how Veritas Prep can help you achieve a great GMAT score by checking out their GMAT Prep Options >



NonHuman User
Joined: 09 Sep 2013
Posts: 13241

Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
Show Tags
15 Oct 2018, 06:26
Hello from the GMAT Club BumpBot! Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up  doing my job. I think you may find it valuable (esp those replies with Kudos). Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________




Re: Let the function g(a, b) = f(a) + f(b).
[#permalink]
15 Oct 2018, 06:26






